KEAMANAN BASIS DATA MENGGUNAKAN ENKRIPSI DATA PADA SISTEM INFORMASI KEUANGAN - Rahmadilla Nurul Fandini Lubis; Muhammad Irwan Padli Nasution (JURNAL ILMIAH NUSANTARA, 2025)
Financial information systems are vital components in managing an organization's financial data, making them highly vulnerable to security threats such as data theft and information manipulation. To address these challenges, the implementation of encryption technology has become a primary solution to ensure data confidentiality and integrity. This study aims to analyze various encryption methods used in financial database systems, including RC4,SHA3-512, RSA, and homomorphic encryption algorithms. The research method used is a qualitative approach through literature studies of scientific journals published from 2021 onwards. The results indicate that implementing the right combination of encryption algorithms can enhance protection against cyber-attacks and maintain the privacy of financial data optimally. These findings emphasize the importance of encryption-based security systems in supporting the reliability and user trust in financial information systems.